An Opponent-Process Theory of Motivation - Solomon, Richard L.; Corbit, John D. (American Economic Review, 1978)
The paper by Solomon and Corbit is regarded by many psychologists as the most successful attempt so far of providing a general theory capable of explaining both psychological addiction and some people's acquired taste for exposing themselves to extreme danger. Apart from the omission of two somewhat technical sections, in which the authors relate their hypothesis to Pavlovian conditioning, the paper is reprinted in full. It is the first of a series of articles: the one which presents the hypothesis and gives an overview of its applications. The subsequent articles contain accounts of experiments designed to test the hypothesis. The behavioral hypothesis is clearly one the postulate of consumer rationality cannot very well explain. Addiction, like externalities and non-convexities, is one of those awkward exceptions that do not fit into the economist's standard models. We might, perhaps, be excused for ignoring it, if addiction were confined to a few chemical substances and due to physiological causes; but there is a growing suspicion of its being a much more general phenomenon. The psychologists' motivation theory has a large overlap with our theory of consumer preference; the Solomon and Corbit article has been chosen as a good example of their approach to a problem we have not yet considered though are likely, sooner or later, to feel compelled to consider. The approach of the article differs from and should supplement that of the more general theory of motivation which is built around the concept of arousal and formed the core of Scitovsky's account of the psychologists' view of individual behavior.